The impact of green finance on improving the financial performance of traditional commercial banks (Field study in Lattakia Governorate) - محمد , رامي (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to determine the impact of green finance of all kinds (short-term finance, medium-term finance, long-term finance) in improving the financial performance of traditional commercial banks in Lattakia Governorate. The study followed the analytical descriptive approach, and a set of methods, including relying on secondary and primary data, through a questionnaire that was designed and distributed to (97) respondents, (93) were recovered from them, and (89) questionnaires were valid for analysis, and the research community consisted of the cadre of workers in The upper administrative levels of the branches of the traditional Syrian commercial banks are responsible for the financing decision-making process, then the SPSS program was relied upon as a tool for analyzing the available data. The study reached a number of results, including: There is no significant relationship between green finance and financial performance, as the Pearson correlation coefficient is (0.026), which indicates a weak, almost non-existent, correlation between green finance and financial performance. There is no significant relationship between the types of green finance (short-term finance, medium-term finance, long-term finance) and risk, as the Pearson correlation coefficient reached (0.001, 0.036, 0.290, respectively), which indicates a weak, almost non-existent correlation between the types of green finance and risk. . There is no significant relationship between the types of green finance (short-term finance, medium-term finance, long-term finance) and liquidity, as the Pearson correlation coefficient reached (0.068, 0.065, 0.227), which indicates a weak, almost non-existent, correlation between the types of green finance and liquidity.